TREN GLOBAL PENELITIAN PEMBELAJARAN AL-QUR’AN: ANALISIS BIBLIOMETRIK TERHADAP PENDIDIKAN BERMUTU UNTUK PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM DI INDONESIA - Siti Lutviah Azizah; Bunyamin Bunyamin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research is motivated by the urgency to understand the direction and development of global research trends on Qur’an learning in the context of improving the quality of Islamic education in the digital era. The lack of studies that comprehensively map the dynamics of global research related to Qur’an learning makes this study important as a basis for developing relevant, innovative, and sustainable Islamic education curricula. The main objective of this research is to analyze global scientific publications on Qur’an learning using a bibliometric analysis approach, as well as to identify core themes that contribute to achieving Quality Education (SDG 4). This study employs a descriptive quantitative method with the assistance of Biblioshiny (R Studio) software to map relationships between authors, keywords, and thematic trends based on publications in the Scopus and Google Scholar databases over the past two decades (2015–2025). The research results show that Qur’an learning research is rapidly developing, focusing on the integration of technology, Qur’anic pedagogy, and the enhancement of science-based spiritual literacy. Three main dimensions identified human, science, and curriculum serve as the foundation for integration in developing a contextual Islamic education curriculum in Indonesia. The novelty of this research lies in combining bibliometric analysis with a perspective on Islamic curriculum development based on global evidence, which has not been widely done in the literature. The contribution of this study not only enriches the academic discourse on Qur’an learning but also provides practical recommendations for curriculum designers, educational institutions, and policymakers in realizing an Islamic education that is adaptive to the demands of the times and quality-oriented.